دور اللّعب في تحقيق الصّحة النّفسية للطفل - دولة, خديجة (جامعة الوادي - University of Eloued, 2021)
يعتبر اللّعب ضرورة بيولوجية مهمة تتم به عملية النّمو، والتّطور يكتسب به الطفل مهاراته الحركية، ويتقوى جسمه، ويقوم بعمليات معرفية من استطلاع، واكتشاف، واستدعاء للصور الذهنية، والرموز، والمفاهيم. فهو وسيلة للتعبير عن الذات، والكشف عن قدراتها، ومواهبها، وهو رمز الصّحة العقلية، والنّفسية، والجسدية للطفل الذي يمارسه. حيث أنّ التّمتع بالصّحة النّفسية في سن الرّشد، يتوقف إلى حد بعيد على الطفولة. الّتي يجب تجاوز مختلف مراحلها بنجاح. لذا هدف بحثنا لإبراز دور اللّعب في تحقيق الصّحة النّفسية للطفل. تطرقًا لماهية الصّحة النّفسية، وفوائد اللعب، ووظائفه، ثم التّناول لدور اللّعب في صحة الطفل النّفسية. ومن أهم ما اقترحناه توعية أفراد المجتمع بأهمية اللّعب، والتأكيد على دوره في النمو السليم للطفل، وتشجيع الهيئات العلمية لإجراء البحوث والدراسات في مجال اللعب، وتزويد المدارس بساحات، وقاعات مخصصة للّعب. Abstract Play is an important biological necessity in which the process of growth and development, the child acquires his motor skills, his body is strengthened, and performs cognitive processes of reconnaissance, discovery, and recall of mental images, symbols, and concepts. It is a means of self-expression, revealing its abilities, and its talents, a symbol of mental, psychological, and physical health of the child, practiced by him. The enjoyment of mental health at the age of majority depends to a large extent on childhood. That you must successfully bypass its various stages. So, our aim is to highlight the role of play in achieving the child's mental health. Address what mental health, the benefits of play, and its functions, and then take part in the role of play in the child's mental health. The most important thing we have proposed is to educate the community about the importance of play, to emphasize its role in the healthy development of the child, to encourage scientific bodies to conduct research and studies in the field of play, and to provide schools with squares and play halls.
مقال
Keywords: الصّحة النّفسية، الصّحة النّفسية للطفل; psychological health, Child's psychological health